The Spanish Withdrawal from Iraq (2004) and Defence Awareness (Comillas Journal of International Relations, 2022)
National defence awareness is a key element in the defence of a state. In Spain, all governments have made it a priority objective to strengthen it. In the period 2001-2007, Defence and the Armed Forces reached maximum levels of notoriety and media presence while the conflicts in Iraq and Afghanistan arose, where international contingents were deployed, which caused some sectors of public opinion to see them as neo-colonial conflicts. This view has made it difficult to see them from other perspectives and provoked public rejection. The withdrawal of the Spanish contingent in Iraq after a terrorist attack had a significant impact on defence awareness.
Keywords: Iraq; Zapatero; defence awareness; public opinion